High-resolution anorectal manometry for diagnosing obstructed defecation syndrome associated with moderate rectocele compared to healthy individuals - Hong Zhi Geng; Yi Zhang; Chen Xu; Jiying Cong; Yuwei Li (BMC Gastroenterology, 2024)
Abstract Background Few studies have investigated healthy female individuals (HFI) and those with obstructed defecation syndrome associated with moderate rectocele in women (MRW), identified using three-dimensional high-resolution anorectal manometry (3D HRAM) parameters that correlate with age stratification. Objective We aimed to explore the clinical diagnostic values of the MRW and HFI groups using 3D HRAM parameters related to age stratification. Methods A prospective non-randomized controlled trial involving 128 cases from the MRW (treatment group, 68 cases) and HFI (control group, 60 cases) groups was conducted using 3D HRAM parameters at Tianjin Union Medical Center between January 2017 and June 2022, and patients were divided into two subgroups based on their ages: the ≥50 and < 50 years subgroups. Results Multivariate binary logistic regression analysis showed that age (P = 0.024) and rectoanal inhibitory reflex (P = 0.001) were independent factors affecting the disease in the MRW group. Compared to the HFI group, the receiver operating characteristic (ROC) curve demonstrated that the 3D HRAM parameters exhibited a higher diagnostic value for age (Youden index = 0.31), urge to defecate (Youden index = 0.24), and rectoanal pressure differential (Youden index = 0.21) in the MRW group. Conclusions Compared to the HFI group, the ROC curve of the 3D HRAM parameters suggests that age, urge to defecate, and rectoanal pressure differential in the MRW group have a significant diagnostic value. Because the Youden index is lower, 3D HRAM cannot be considered the gold standard method for diagnosing MRW.